Networks and knowledge at the interface; Governing the coast of East Kalimantan - Kusumawati, Rini (Wacana, Journal of the Humanities of Indonesia, 2016)
The thesis explores the actual processes of interaction between global and local actors regarding marine conservation and aquaculture development. The objective of the thesis is to analyse the collaboration, friction, and the cultural-historical, social, political, and economic contestations of the value and meaning of conservation from the perspectives of the district governmental agencies, the district head, local entrepreneurs and industry, and the international NGO. Concentrating on the dynamics of this global-local interface this thesis adds to existing literature because it helps us to understand why global environmental networks often face contention and even fail to be effective in their attempts to implement regulations or standards for a more sustainable production of coastal resources. The data were gathered during long-term anthropological fieldwork combining a political-ecology approach with environmental anthropology.